PENGARUH PERPUTARAN MODAL KERJA DAN RASIO HUTANG TERHADAP PROFITABILITAS PADA PT. JASA ASURANSI INDONESIA (PERSERO) - Riana Febriyanti; Sunu Puguh Hayu Triono (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
This study uses descriptive and verificative methods. The sample in this study amounts 20 data that taken by purposive sampling technique. Collecting data uses documentation, library research, and internet research, in data managing uses regression linear analysis, analysis castellation Pearson, determination, f-test and t-test, statistic data managing uses program addition such as Excel and SPSS 20 For Windows. The study result shows that Work Capital and Debt Ratio Turnover has strong relationship through profitability. And it has influence as big as 8.40%. Then from such study result, partially correlation for work capital turnover with profitability, positive, then positive correlation value shows the relationship between revert variable. Where, if more and more small or decrease work capital turnover value, resulted profitability more and more large or high or obtained the number of profit. So that debt ratio has influence as big as 7.78%. Furthermore, from computation result determination coefficient with contribution as big as 70% while reminder 30% are influenced by other factors such as storage, fixed asset, trade cost (general & administration costs, and other costs). Keywords: Work Capital Turnover Debt Ratio, Profitability